Identification Of Plants With Medicinal Efficacy Based On Local Knowledge Of The Community Of Rano Jaya Village, Toari District, Kolaka District - Pratiwi, Pratiwi; Valentina, Ana; Saparuddin, Saparuddin; Ernawati, Ernawati; Fadilah MgB, A; Nurjanah, Niken; Fitri, Nur; Akila, Nur; Maretik, Maretik (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
Indonesian people have long used traditional medicinal ingredients as alternative medicine before the existence of modern health services. Ancestors' lives in harmony with nature foster awareness that nature provides medicine for themselves and society.Traditional medicines generally come from plants, although some ingredients come from animals. This treatment has been carried out for generations, but has not been officially recorded by the government and has not been scientifically documented. This research aims to provide scientific information regarding the use of medicinal plants, as well as identifying the types of plants, parts used, and how they are processed by the community in Rano Jaya Village, ToariDistrict, Kolaka Regency. The research method used is descriptive qualitative, namely providing an overview of the object being studied in natural conditions. The research results identified 30 types of plants from 23 families that were known to the public as medicinal, with positive perceptions regarding the safety of consuming medicinal plants. The most widely used plant parts are leaves (47.5%) and fruit (17.5%). The common processing methods are boiling (46.5%) and mashing (18.6%). The percentage of utilization of other plant parts includes seeds (5%), stems (15%), roots (2.5%), flowers (2.5%), and tubers (10%). These findings emphasize the importance of local knowledge about medicinal plants for public health and the preservation of traditions and biodiversity.